PERAN KELUARGA DALAM PEMBENTUKAN IDENTITAS GENDER DAN BUDAYA DI ERA GLOBALISASI - Hasibuan, Rosari Damayanti; H, Kurniawan; Sampurna Siregar; Nursania Dasopang (LPPM STAI Muhammadiyah Probolinggo, 2025)
Abstract The family plays a crucial role in shaping a child's gender and cultural identity from an early age. As the first social unit, the family teaches values, norms, and expectations related to gender roles and culture, which influence how children perceive themselves. In the context of globalization, the family's role becomes increasingly complex due to the influence of media, technology, and cross-cultural interactions that introduce new perspectives and norms. This study aims to investigate how families contribute to shaping children's gender and cultural identity amid the influences of globalization. The research employs a qualitative approach with a descriptive design. The findings indicate that children's gender identity is formed through parenting styles, communication, and social expectations imposed by parents. However, global media exposure often introduces foreign cultures that may blur local values. To address this, families need to play an active role by fostering critical thinking in children, strengthening local identity through arts and traditions, and creating space for healthy discussions on changing gender and cultural norms. By doing so, families can help children integrate traditional and modern values, enabling them to navigate the challenges of globalization without losing their sense of identity. Keywords: Family, Gender Identity and Culture, Globalization